ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN DANA ZAKAT PADA ORGANISASI PENGELOLA ZAKAT DI INDONESIA - Muhammad Ziadatul Khaq; Ika Khusnia Anggraini (Islamic Economics and finance in Focus, 2024)
Poverty is one of the unresolved problems in Indonesia. This problem should be overcome, one of the ways, is through Islamic philanthropy, especially zakat. The gap between the potential and realization of zakat, the less than optimal performance of zakat institutions has resulted in low public trust so that supervision is needed by various parties so that zakat can be managed well. Therefore, this research aims to analyze the effectiveness and efficiency of zakat fund management performance in Zakat Management Organizations (OPZ) in Indonesia. This type of research is descriptive quantitative research that uses the ACR (Allocation to Collect Ratio) method to measure effectiveness and the DEA (Data Envelopment Analysis) method to measure efficiency. The data is in the form of secondary data originating from the annual financial reports of BAZNAS, Dompet Dhuafa, and Rumah Zakat from 2018 to 2021. The results of the study show that in general the three OPZs received high effectiveness and efficiency scores. BAZNAS is the most effective OPZ and Rumah Zakat is the most efficient OPZ. So it can be used as the main reference for other OPZs in efforts to improve the performance of zakat management in Indonesia.